Effect of nursing interventions on preventing side effects of azacitidine in patients with high-risk myelodysplastic syndrome (预防较高危骨髓增生异常综合征患者阿扎胞苷治疗所致不良反应的护理效果观察) - WANG Xue (王雪); CAO Hongjing (曹红京); LI Ning (李宁); CHEN Siyu (陈思雨); REN Lixin (任利鑫); SONG Meijia (宋美佳) (Association of Integrative Nursing, 2022)
Objective To investigate the effect of predictive nursing strategies on preventing side effects of azacitidine in patients with high-risk myelodysplastic syndrome. Methods Totally 40 patients undergoing subcutaneous injection therapy with azacitidine for high-risk myelodysplastic syndrome were randomly divided into the observation group and control group, with 20 cases in each group. Routing nursing management including posture nursing, oral care, psychological care and nursing of adverse reactions was carried out in the control group. In the observation group, a special nursing team was set up to enhance the predictive nursing interventions such as nutrition support, prevention of infection and hemorrhage, and so on. The side effects of azacitidine therapy were observed analyzed. Results The incidence of adverse reactions in the observation group was significantly lower than that in the control group (10. 00% vs. 45. 00%, P＜0. 05). Conclusion For those patients undergoing subcutaneous injection therapy with azacitidine for high-risk myelodysplastic syndrome, the predictive nursing is potentially effective to reduce the incidence of adverse drug reactions. (目的 探讨预见性护理干预预防较高危骨髓增生异常综合征患者阿扎胞苷治疗所致不良反应的效果。方法 40例较高危骨髓增生异常综合征患者随机分为观察组(n=20)和对照组(n=20)。两组患者均给予阿扎胞苷皮下注射治疗。对照组实施常规护理, 包括体位护理、口腔护理、心理护理和不良反应护理; 观察组实施预见性护理干预, 成立预见性护理小组, 强化营养干预、感染预防、出血预防等护理措施。比较两组不良反应发生情况。结果 观察组不良反应发生率10. 00%(2/20), 低于对照组的45. 00%(9/20), 差异有统计学意义(P＜0. 05)。结论 对较高危骨髓增生异常综合征患者, 应用阿扎胞苷治疗的同时配合预见性护理, 可以有效降低不良反应的发生风险。)